GANGGUAN BERBAHASA PESERTA DIDIK DALAM PERSPEKTIF NEUROPENDIDIKAN: FAKTOR GENETIK, NEUROLOGIS, DAN STRATEGI PEMBELAJARAN - Said, Sayuthi Atman; Amrah Kasim; Baso Pallawagawu; Ahmad Munawwir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines learner language disorders from a neuroeducational perspective by connecting genetic vulnerability, neurological language processing, and pedagogical responses. The study addresses the tendency to interpret language difficulties merely as low motivation, poor discipline, or instructional failure, although persistent language disorders may arise from complex interactions among biological, cognitive, environmental, and educational factors. A qualitative library-research design was employed. Twenty-four peer-reviewed articles published mainly between 2019 and 2025 were selected from international databases and Indonesian nationally accredited journals, while several foundational publications were retained to clarify core concepts. The sources were analyzed through identification, thematic coding, comparison, interpretation, and synthesis. The review shows that neuroeducation is an interdisciplinary field integrating neuroscience, cognitive psychology, and education to translate evidence about brain development and learning into responsible pedagogical decisions. Genetic factors indicate susceptibility rather than predetermined failure, whereas neurological differences may affect phonological processing, vocabulary, verbal working memory, comprehension, and literacy. Accordingly, educational institutions need early and continuous identification, explicit and differentiated language instruction, multisensory support, flexible assessment, selective use of digital interventions, and collaboration among teachers, families, and professionals. The article contributes an integrative framework that links biological vulnerability with inclusive educational support while warning against genetic determinism, labeling, and uncritical neuromyth-based practices.